Pemilihan Alternatif Terbaik Dalam Pengembangan Produksi Kerupuk Pati Menggunakan Metode SAW - Vio Pradani Kusuma Wardana; Dewi Restiana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
We often find snacks such as crackers that are traded around us with various flavors and shapes, in conditions like this forcing cracker business actors to provide their best cracker products. To make a good product must be included with the best alternative decision in determining the future steps. There are methods that can be used to determine the best alternative decision, one of which is the SAW (simple additive weighting) method. The value with the highest ranking is recommended in determining the best alternative decision. In a study conducted on the Bu Yuliana cracker business, Mulya Agung Village, Kec. Antang Kalang, East Waringin City, there are criteria that can be used to determine the best alternative. Thus the final decision can be obtained from the ranking with the highest number of values, namely 1.15 which is contained in the V3 alternative.